Business Planning : Crystal livestock industry / Nor Anida Hasan ...[et al.] - Hasan, Nor Anida; Sahak, Nur Syamsila; Omar, Norma Liyana; Mohd Saudi, Siti Harul Aini (2009)
Feedlot livestock gives special care to cattle intensively in barn for the purpose of feedlot cattle production through the improvement of its weight by giving sufficient quality food, clean water, mineral and vitamin in some period of time